Online Podcast Production as Co-Creation for Intercultural Participation in Neighbourhood Development - Barbarino, Robert (2022)
This article describes the usage of an online podcast workshop as an arts-based research method to reflect on intercultural participation. The podcast workshop was co-developed by researchers, local civil society actors, and administrative employees and deployed in a research infrastructure based on real-world labs. We show how the online podcast workshop as a research tool elicits co-creation with agonistic as well as communicative practices. The podcast combined practices of making with socially engaged research, using digital storytelling. It aimed at enhancing intercultural dialogue and participation and was used as an opportunity for voices that are not sufficiently represented in local public discourse on neighbourhood development to become recognised and challenge marginalisation. Based on one online podcast workshop, the article addresses new possibilities for collective and collaborative action during the Covid-19 pandemic and frames the podcast as a moderated place for exchange and reflection in the digital space. The podcast workshop intended to foster further discussion on the topic of intercultural participation and was conceived as a tool for empowerment that participants can use for further conversations and exchange in their communities.